Quadro Editorial (Estudos em Design, 2021)
EditoresCristina PortugalRita Maria de Souza CoutoAvaliadores desta edição v. 29, n. 2 (2021)Adriana GralowAlexandre FarbiarzÁlvaro José Barbosa SousaAna Veronica PazminoAndré Ribeiro de OliveiraAndréa SilvaAngélica AdverseAntônio Ferreira Colchete FilhoBeany MonteiroCássia Letícia CarraraClice MazzilliClaudio SilvaCristina PortugalCyntia Santos MalagutiDaniel PortugalDaniel RaposoDaniela AlvesDeborah ChristoDoris KosminskyEdson Rufino de SouzaEloiza Andrade CorrêaElizabeth RomaniEverton da SilvaFernando Fogliano Frederico Braida Gabriel PatrocínioGisela de CamposHaroldo GalloHelena BastosHelena NeumannJade PiaiaJamille Noretza de Lima LanuttiIone Maria Ghislene BentzJoao Eduardo chagas SobralJosé Carlos da SilvaJuliana BuenoKando FukushimaKátia Carvalhaes PêgoKatia MillerLeticia Affini Letícia Pedruzzi Fonseca Linda LinnLuiz AgnerMárcio GuimarãesMarcos BragaMaria Cristina IbarraMariana Cantisani PaduMariano Lopes de Andrade NetoMaristela Mitsuko OnoNelson KuwaharaOtniel Josafat López AltamiranoPaula LadinRafaella PeresRanielder Fábio de FreitasRaquel NoronhaRavi PassosRenata CadenaRicardo Cunha LimaRogério José CâmaraRomero ToriSandra SouzaSérgio Luciano da SilvaTiago Barros Pontes SilvaVera DamazioVerônica FreireVirginia KistmannViviane NunesWagner BandeiraWalter Neto